Characterizing monoclonal antibody epitopes by filtered gene fragment phage display - Di Niro, Roberto (2005)
In the present paper, we describe a novel approach to map monoclonal antibody epitopes, using three new monoclonal antibodies that recognize h-TG2 (human transglutaminase 2) as an example. The target gene was fragmented and cloned upstream of an antibiotic-resistance gene, in the vector pPAO2, to select for in-frame polypeptides. After removal of the antibiotic-resistance gene by Cre/Lox recombination, an antigen fragment phage display library was created and selected against specific monoclonal antibodies. Using the h-TG2 fragment library, we were able to identify epitopes. This technique can also be broadly applied to the study of protein-protein interactions.